2004
DOI: 10.1161/01.hyp.0000113295.31481.36
|View full text |Cite
|
Sign up to set email alerts
|

Renal Oxidative Stress in Medullary Thick Ascending Limbs Produced by Elevated NaCl and Glucose

Abstract: Abstract-The effects of NaCl, glucose, and thyroid hormone on the production of superoxide (O 2 ·Ϫ ) within the renal medulla of Sprague-Dawley rats were examined. Responses of intracellular superoxide [O 2 ·Ϫ ] i in isolated medullary thick ascending limbs (mTALs) were studied using real-time fluorescent microscopy with measurement of the dehydroethidium (DHE) to ethidium (Eth) conversion ratio (Eth/DHE ratio unit). The results demonstrated that elevations of extracellular NaCl (from 152 to 252 mmol/L), D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 41 publications
6
72
0
1
Order By: Relevance
“…Increased salt may induce oxidative stress, independent of a change in blood pressure, because a salt load increased NADPH oxidase O 2 ⅐Ϫ production in tissue strips of medullary thick ascending limb. 37 In vivo, Sprague Dawley rats fed a high-salt diet did not develop hypertension but exhibited increased urinary 8-isoprostane excretion and renal cortical gp91 phox and p47 phox subunit mRNA expression. 38 Although it has been shown that NADPH oxidase subunits are upregulated in SS rats fed a high-salt diet, 15 no study has previously shown an elevation in renal medullary NADPH oxidase in SS rats on a normal salt diet.…”
Section: Taylor Et Al Renal Medullary Nadph Oxidase and Hypertensionmentioning
confidence: 98%
“…Increased salt may induce oxidative stress, independent of a change in blood pressure, because a salt load increased NADPH oxidase O 2 ⅐Ϫ production in tissue strips of medullary thick ascending limb. 37 In vivo, Sprague Dawley rats fed a high-salt diet did not develop hypertension but exhibited increased urinary 8-isoprostane excretion and renal cortical gp91 phox and p47 phox subunit mRNA expression. 38 Although it has been shown that NADPH oxidase subunits are upregulated in SS rats fed a high-salt diet, 15 no study has previously shown an elevation in renal medullary NADPH oxidase in SS rats on a normal salt diet.…”
Section: Taylor Et Al Renal Medullary Nadph Oxidase and Hypertensionmentioning
confidence: 98%
“…62 When the juxtamedullary glomeruli are injured by hypertension, the impairment of oxygen delivery downstream from the vasa recta vessels would be expected to result in tubulointerstitial injuries in the outer medulla. Superimposed on these factors, a number of other elements, including neurohormonal factors, 56 inflammatory pathways, 53 oxidative stress 63,64 and tubular transport, 65,66 are involved in the pathogenesis of the injuries, among which tubulovascular crosstalk is of particular interest. 63,64,67,68 We have recently shown that an increase in tubular transport at the mTAL enhances superoxide production and reduces nitric oxide synthesis.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 99%
“…In contrast, exposure of isolated PTCs to fatty acid-conjugated albumin induced mitochondrial ROS production that was reversed with rotenone and not by NAD(P)H oxidase or XO inhibitors (139). Further to elucidate the importance of redox mechanisms in the kidney, pericytes of intact vasa recta (VR) were compared with pericytes of VR with disrupted endothelium for Ang II-mediated superoxide production (221). Interestingly, Ang II did not increase superoxide production in either scenario; however, addition of an NO scavenger led to increased superoxide production in endothelium-denuded vessels, suggesting crosstalk between different cell types, which is inhibited by antioxidants (NO).…”
Section: B Ros and The Glomerular Basement Membrane (Gbm)mentioning
confidence: 99%